2013
DOI: 10.1177/0363546513496626
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Morphological Evaluation of the Quadriceps Tendon Using 3-Dimensional Magnetic Resonance Imaging Reconstruction

Abstract: The quadriceps tendon has the anatomic characteristics to produce a graft whose length and volume are both reproducible and predictable, while yielding a graft with a significantly greater intra-articular volume than a patellar tendon graft with a similar width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 34 publications
4
89
6
Order By: Relevance
“…The quadriceps tendon is consistent in size, having the anatomic characteristics to produce a graft whose length and volume are both reproducible and predictable. 11 Using a free boneeharvesting technique eliminates the risk of iatrogenic patellar fracture and has minimal donor-site morbidity. This technique does not require any special instruments and is relatively minimally invasive.…”
Section: Discussionmentioning
confidence: 99%
“…The quadriceps tendon is consistent in size, having the anatomic characteristics to produce a graft whose length and volume are both reproducible and predictable. 11 Using a free boneeharvesting technique eliminates the risk of iatrogenic patellar fracture and has minimal donor-site morbidity. This technique does not require any special instruments and is relatively minimally invasive.…”
Section: Discussionmentioning
confidence: 99%
“…The quadriceps tendon also produced a graft with almost twice the intra-articular volume of that from the patellar tendon. 15,34,39,46,47 Recent unpublished studies by Xerogeanes et al have shown that a matched-width quadriceps tendon graft had an ultimate load 28% higher than a patellar tendon from the same specimen. The quadriceps tendon also had a Young modulus that was similar to the native ACL, whereas that of the patellar tendon was significantly higher and that of the double-looped semitendinosus/gracilis graft was significantly lower than the native ACL.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound measurements of skeletally immature patients reveals predictable increases in QT thickness relative to age, height and weight 16. Moreover, a separate analysis showed height to be the most important predictor of length of the tendinous portion of the QT graft among a cohort of patients, 34.9±12.6 years of age (range: 17–60 years) 15. These relationships can be used preoperatively to verify that the harvested autograft will be of sufficient diameter and length to accommodate ligamentous reconstructions.…”
Section: New Information On Anatomymentioning
confidence: 97%
“…The width of the tendon ranges between 2.5 and 3 cm, with the greatest width found approximately 3 cm proximal to the tendon’s insertion on the patella 13–15. Additionally, the thickness of the QT is greatest at its distal insertion on the patella, measuring 18±3 mm in males and 16±2 mm in females 15. The tendon’s thickness remains relatively constant throughout the distal 6 cm, measuring 7.4 mm, 7.4 mm and 7.1 mm at 10, 30 and 60 mm proximal to its distal insertion 15…”
Section: New Information On Anatomymentioning
confidence: 98%